The impact of 25-hydroxyvitamin D and calcium on risk of age-related macular degeneration: a Mendelian randomization study - Dong, Xing-Xuan (2024)
Background: The relationships between 25-hydroxyvitamin D [25(OH)D] and calcium and age-related macular degeneration (AMD) are unclear. Objectives: This study aimed to investigate the causal role of 25(OH)D concentrations, calcium concentrations, and dietary supplements use of vitamin D and calcium on the risk of AMD and its subtypes. Methods: Independent genetic variants associated with 25(OH)D and calcium concentrations were used as instrumental variables in published genome-wide association studies (GWASs) of European ancestry. The bidirectional 2-sample Mendelian randomization (MR) analyses were performed using summary-level data from the UK Biobank and FinnGen datasets. Sensitivity analyses were conducted to ensure the robustness of the MR results. The meta-analyses were conducted using fixed and random-effect models to provide comprehensive and reliable estimates. Results: A standard deviation increase in calcium concentrations was linked to a 14%, 17%, and 13% reduction in the likelihood of developing AMD (95% confidence interval [CI]: 0.77, 0.97), wet AMD (95% CI: 0.73, 0.95), and dry AMD (95% CI: 0.75, 1.00), respectively. No significant causal relationships were detected between genetically predicted 25(OH)D concentrations and AMD and its subtypes (all P > 0.05). The combined analyses showed that higher calcium concentrations were associated with a reduced risk of overall AMD, with an odds ratio of 0.89 (95% CI: 0.81, 0.98). Conclusions: This study supports the causal relationship between calcium concentrations and the risk of AMD and its subtypes, which may have important implications for the prevention, monitoring, and treatment of AMD.